1975
DOI: 10.1159/000117480
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Symptoms in Pre-Menstrual Tension to Oestrogen and Progesterone Concentrations in Blood Plasma

Abstract: 15 women with premenstrual tension are rated in four symptom groups, anxiety-tension, asthenia-depression, irritability-explosiveness and feelings of swelling. The ratings of anxiety and irritability were also added to a separate group. Ratings were then correlated to plasma oestrogen and progesterone levels and oestrogen/progesterone ratios. There was a significant correlation between oestrogen levels and the anxiety, irritability, anxiety + irritability and depression groups. A correlation was also found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 14 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…Low luteal phase levels of progesterone together with normal or high levels of estrogen production were reported by Backstrom and associates (46,47) and Brush (48). Backstrom and Mattson (49) found anxiety and irritability symptoms in particular to be correlated with plasma estrogen levels and concluded that the estrogen factor is important for the development of psychologic symptoms in the premenstruum. In a more recent study Backstrom et al (50) found no difference in hormone levels in women with high and low degrees of mood change.…”
Section: Discussionmentioning
confidence: 86%
“…Low luteal phase levels of progesterone together with normal or high levels of estrogen production were reported by Backstrom and associates (46,47) and Brush (48). Backstrom and Mattson (49) found anxiety and irritability symptoms in particular to be correlated with plasma estrogen levels and concluded that the estrogen factor is important for the development of psychologic symptoms in the premenstruum. In a more recent study Backstrom et al (50) found no difference in hormone levels in women with high and low degrees of mood change.…”
Section: Discussionmentioning
confidence: 86%
“…It may be assumed that the PMS group in their study might be less severely affected, especially as regards physical symptoms, than our group taken from an out-patient clinic, a number of whom travelled long distances to attend. Backstrom & Mattsson (1975) considered that oestrogen levels could be correlated with irritability and, to a lesser extent, depression but were unable to correlate bloatedness with any hormonal parameters. The concept of correlation of individual symptoms with specific hormone levels has not been supported by other work.…”
Section: Discussionmentioning
confidence: 98%
“…Although abnormalities of endocrine function are most commonly implicated as the basis of PMS, in ten studies comparing progesterone levels in women with PMS symptoms and controls, five showed reduced mid-to-late luteal phase levels in symptomatic women (Backstrom et al 1976;Backstrom and Carstensen 1974;Munday et al 1981;Abraham et al 1978;Smith 1975), one showed elevated levels (O'Brien et al 1980), and three showed no abnormalities (Taylor 1979;Andersch et al 1979;Anderson et al 1977). Studies of estrogen levels in premenstrual symptoms are equally contradictory, with one study showing a correlation between elevated estrogen levels and symptoms such as anxiety and irritability (Backstrom and Mattsson 1975), but with contradictory reports of elevated estrogen levels, estrogen-progesterone ratios, prolactin levels, and aldosterone levels in PMS sufferers (see Rubinow and Roy-Byrne 1984: 166). Studies of estrogen levels in premenstrual symptoms are equally contradictory, with one study showing a correlation between elevated estrogen levels and symptoms such as anxiety and irritability (Backstrom and Mattsson 1975), but with contradictory reports of elevated estrogen levels, estrogen-progesterone ratios, prolactin levels, and aldosterone levels in PMS sufferers (see Rubinow and Roy-Byrne 1984: 166).…”
Section: The Physiological Basis Of Pmsmentioning
confidence: 99%